2015
DOI: 10.5430/rwe.v6n4p64
|View full text |Cite
|
Sign up to set email alerts
|

Does Foreign Direct Investment (FDI) Really Matter in Developing Countries? The Case of Egypt

Abstract: The main purpose of this paper is to examine the various factors that attract Foreign Direct Investment (FDI) in developing countries, in order to find answers to the following question: Does foreign direct Investment really matters in developing countries? The study investigates the relationship between FDI and the economic growth in Egypt as a good indicator for developing countries, covering the period 1961-2012. Results from the analysis suggest that FDI is explained by some economic determinants but has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This implies that the larger the capital size of FDI firms, the less linkage they have with Vietnamese domestic firms. This result is consistent with the mentioned theory and similar to previous studies, such as Masry (2015).…”
Section: Model Resultssupporting
confidence: 94%
“…This implies that the larger the capital size of FDI firms, the less linkage they have with Vietnamese domestic firms. This result is consistent with the mentioned theory and similar to previous studies, such as Masry (2015).…”
Section: Model Resultssupporting
confidence: 94%
“…Therefore, this works to correct labor market imbalances and build new productive capacities, in order to achieve the ultimate goals of the economic policies of growth and economic prosperity. Over the last two decades, foreign direct investment (FDI) funds from developing countries have grown at an annual average higher than those from developed countries, and their outward stock has increased more than 15 percent of the world's outward stock of FDI compared to less than 10 per cent in the 1990s [8,9]. Globally, foreign direct investment plays an important role in transferring the new technology to the host country and accordingly leads to higher productivity and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the impact of FDI on host country economic growth, Agrawal (2015), Agrawal and Khan (2011), Iamsiraroj and Ulubaşoğlu (2015), Soltani and Ochi (2012) have found positive significant relationship while Akinlo (2004), Azman-Saini et al (2010), Masry (2015) have found weak connection. Furthermore, Herzer et al (2008) challenged the common belief of the positive impact of FDI on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the economic literature, the relationship between FDI and economic growth is ambiguous. Some researchers have found significant positive association (Agrawal, 2015;Bengoa & Sanchez-Robles, 2003;Fedderke & Romm, 2006;Hansen & Rand, 2006) between FDI and host country economic growth while some others have found weak or insignificant relationship (Belloumi, 2014;Haruna Danja, 2012;Masry, 2015). Hence, the sign and the level of significance of the coefficient of FDI with industrial sector performance have to be tested empirically in the Sri Lankan context.…”
Section: Data Sources and Variable Descriptionmentioning
confidence: 99%